Hubungan Indeks Massa Tubuh Dan Asupan Natrium Dengan Tekanan Darah Pada Penderita Hipertensi Rawat Jalan Di RSUD Dr. Moewardi Surakarta - KHOTIMAH, Nuning; , Elida Soviana, S.Gz., M.Gizi; , Dr. Listiana Dharmawati S., M.Si (2015)
Backgroud. Hypertension is upnormal of blood pressure >140mmHg systolic and >90mmHg diastolic. There are some affect blood pressure one body mass index will cause the volume of blood vessels is increased so as to give greater pressure on the artery wall excess sodium will increase blood, cardiac output and blood pressure. Objective. This study research aimed to know the relationship between body mass index and sodium intake with blood pressure in out-patient with hipertension of Dr. Moewardi hospital in Surakarta Research Methods. Type of research was an observational study with cross sectional design. There were 24 respondents who chosen by consecutive sampling technique. Body mass index data were obtained by measurement of weight and heigth ,where as sodium intake data obtained by using food recall 3 x 24 hours, while blood pressure medi records obtained from the study subjects. Correlation test used was Pearson Product Moment test and Rank Spearman test. Results. As much as 66.7% of respondents had body mass index. As much as 45,8% had sodium intake. There was no association between (p-value = 0.679) and sodium intake (p-value=0.998) with blood pressure in hypertensive patients outpatient Hospital Dr. Moewardi Surakarta. Conclusion.There was no association between body mass index and intake of sodium with blood pressure in patients with hypertension outpatients Hospital Dr. Moewardi at Surakarta.